2006
DOI: 10.1097/01.ijg.0000212294.31411.92
|View full text |Cite
|
Sign up to set email alerts
|

Three and Five Year Changes in Intraocular Pressures After Clear Corneal Phacoemulsification in Open Angle Glaucoma Patients, Glaucoma Suspects, and Normal Patients

Abstract: This study demonstrates that cataract removal by clear cornea phacoemulsification in glaucoma patients, glaucoma suspects, and normal patients results in a small but significant decrease in IOP that is sustained at 3 years and a mean of 5 years in all groups. This study does not imply that cataract removal by phacoemulsification is a substitute for a combined procedure but may be an appropriate procedure for certain patients based on medication requirements and extent of optic nerve damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
144
4
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(179 citation statements)
references
References 21 publications
10
144
4
8
Order By: Relevance
“…In this study, perhaps the most alarming report was the fact that almost 40% of these glaucoma patients lost IOP control during the first year after cataract surgery either because they needed more medication (or laser) or because of an IOP increase (in cases where there was no change in medication regimen). Very similar results had previously been demonstrated by Shingleton et al (13) in a study with fewer patients but with longer follow-up time (average of 5 years). Finally, we must also highlight the effects of cataract surgery on IOP in the first few days after surgery.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…In this study, perhaps the most alarming report was the fact that almost 40% of these glaucoma patients lost IOP control during the first year after cataract surgery either because they needed more medication (or laser) or because of an IOP increase (in cases where there was no change in medication regimen). Very similar results had previously been demonstrated by Shingleton et al (13) in a study with fewer patients but with longer follow-up time (average of 5 years). Finally, we must also highlight the effects of cataract surgery on IOP in the first few days after surgery.…”
supporting
confidence: 78%
“…In general, a modest IOP reduction was observed after uncomplicated phacoemulsification in these patients. Among the more rigorous studies, the mean long-term changes in IOP values varied between 1.5 and 2 mmHg (11)(12)(13) . For example, in a recent study by Slabaugh et al (12) , over 150 patients with open-angle glaucoma controlled with medication underwent cataract surgery.…”
mentioning
confidence: 99%
“…No significant difference was found among the values at four months, 2.5 years, and seven years. 15 Other long-term studies have shown a drop in IOP of about 3 mmHg in POAG patients and nonglaucoma patients with 75-85% of patients maintaining an IOP reduction at five years, [16][17][18][19][20] in comparison to our study which showed IOP reduction for just one month post cataract surgery. The method of cataract extraction may influence the reduction of IOP.…”
contrasting
confidence: 48%
“…Geçirilmiş katarakt cerrahisi sonrası iris-lens diyaframının artmış vitreus volümüne bağlı ortaya çıkan kompresyona karşı direncinin düşmüş olabileceğini ve bu nedenle de psödofakik hastalarda fakik hastalara göre daha fazla GİB artışı olabileceğini dü-şünmekteyiz. Çeşitli çalışmalarda katarakt cerrahisi sonrası açı bölgesinin genişlediği gösterilmiştir [13][14][15]. Bu anatomik değişikliğin dışa akımı kolaylaştı-rabileceği göz önünde bulundurulursa çalışmamız-da tespit ettiğimiz 24. saatte psödofakik hastalarda neden daha belirgin GİB düşüşü olduğu daha kolay anlaşılabilir [16,17].…”
Section: Discussionunclassified